2013
DOI: 10.1104/pp.113.221788
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Two Arabinosyltransferases from Tomato Reveals Functional Equivalency of Xyloglucan Side Chain Substituents    

Abstract: Xyloglucan (XyG) is the dominant hemicellulose present in the primary cell walls of dicotyledonous plants. Unlike Arabidopsis (Arabidopsis thaliana) XyG, which contains galactosyl and fucosyl substituents, tomato (Solanum lycopersicum) XyG contains arabinofuranosyl residues. To investigate the biological function of these differing substituents, we used a functional complementation approach. Candidate glycosyltransferases were identified from tomato by using comparative genomics with known XyG galactosyltransf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
85
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(91 citation statements)
references
References 53 publications
5
85
1
Order By: Relevance
“…Such results are consistent with previous studies suggesting that the F side chain Gal accounts for the bulk of the O-acetylated glycoses in Arabidopsis leaf XyG (Pauly et al, 2001;Perrin et al, 2003). Our NMR data indicate that mur3-1 and mur3-2 XyGs contain approximately 7% and 14%, respectively, of the F side chain present in wild-type plants (Supplemental Table S1) and are consistent with the results of recent studies indicating that small amounts of the F side chain are present in the xyloglucan isolated from the mur3-1 mutant (Jensen et al, 2012;Schultink et al, 2013;Vinueza et al, 2013).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Such results are consistent with previous studies suggesting that the F side chain Gal accounts for the bulk of the O-acetylated glycoses in Arabidopsis leaf XyG (Pauly et al, 2001;Perrin et al, 2003). Our NMR data indicate that mur3-1 and mur3-2 XyGs contain approximately 7% and 14%, respectively, of the F side chain present in wild-type plants (Supplemental Table S1) and are consistent with the results of recent studies indicating that small amounts of the F side chain are present in the xyloglucan isolated from the mur3-1 mutant (Jensen et al, 2012;Schultink et al, 2013;Vinueza et al, 2013).…”
supporting
confidence: 91%
“…Arabidopsis fut1, xlt2, and xxt1 to xxt5 mutants that form structurally abnormal XyG (Vanzin et al, 2002;Madson et al, 2003;Perrin et al, 2003;Peña et al, 2004;Jensen et al, 2012;Schultink et al, 2013) or that have reduced Vuttipongchaikij et al, 2012;Zabotina et al, 2012) or no discernible amounts of XyG have no severe developmental or growth phenotypes. This has led plant scientists to question the biological role of XyG in wall assembly and architecture as well as its function in plant growth and development Cosgrove, 2012a, 2012b).…”
mentioning
confidence: 99%
“…Previous studies showed that overexpressing Eucalyptus grandis and tomato MUR3 in the Arabidopsis mur3 and xlt2 mur3.1 mutants also led to XyG overgalactosylation but not complete galactosylation. However, none of these plants were reported to exhibit a dwarfed phenotype (Lopes et al, 2010;Schultink et al, 2013). It, thus, seems that proper functionality of XyG is not retained when XyG galactosylation is below or above a certain threshold, which was found in the mur3 xlt2 double-mutant and the OsMUR3 overexpression lines or mur3-3 knockout plants, respectively.…”
Section: The Rice Genome Contains the Biosynthetic Genes To Generate mentioning
confidence: 97%
“…These data indicate that Os06g12870, termed OsAXY4, exhibits XyG O-acetyltransferase activity but is not functionally equivalent to AtAXY4. The Arabidopsis double-mutant xlt2 mur3.1 contains an XyG that consists predominantly of XXXG (Jensen et al, 2012;Schultink et al, 2013). Expression of the Arabidopsis MUR3 homolog, Os03g05110, in this double mutant resulted in the generation of additional XyG oligosaccharides consistent by mass and retention time with XXLG and XXFG as well as their O-acetylated forms (Supplemental Figs.…”
Section: Impact Of Rice Candidate Genes On Xyg Structures In Arabidopsismentioning
confidence: 99%
“…Ara is also found in xyloglucans of some plant species (9). The XXGG-type xyloglucan found in Solanaceous species is characterized by branches extended with Ara instead of D-galactose (Gal) (10). Ara residues are also critical for signaling processes because mature signaling peptides such as CLAVATA3 require posttranslational arabinosylation in the Golgi apparatus to be biologically active and bind to their receptors (11).…”
mentioning
confidence: 99%